1997
DOI: 10.1159/000227605
|View full text |Cite
|
Sign up to set email alerts
|

A Case-Control Study on Risk Factors for Local Recurrences or Distant Metastases in Breast Cancer Patients Treated with Breast-Conserving Surgery

Abstract: A case-control study was conducted on 143 case-control sets recruited from the 18 key hospitals/institutes in Japan to identify risk factors for local recurrences and distant metastases after breast-conserving surgery in breast cancer patients: (1) positive surgical margin was a risk factor for local recurrences (relative risk (RR) = 16.70, p < 0.001) but not for distant metastases, (2) positive p53 immunostaining was a risk factor for both local recurrences (RR = 5.62, p = 0.003) and distant metastases (RR = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 14 publications
2
14
0
Order By: Relevance
“…After evaluation of several clinico-pathological factors and biomarkers in a case-control study of 66 patients with LR following breast conserving therapy, p53 was found to be an independent predictor of LR [17]. Similar results have been obtained in the study by Turner et al [18] In DCIS, there are not many studies that describe the relation between p53 immunoreactivity and LR.…”
Section: Discussionsupporting
confidence: 72%
“…After evaluation of several clinico-pathological factors and biomarkers in a case-control study of 66 patients with LR following breast conserving therapy, p53 was found to be an independent predictor of LR [17]. Similar results have been obtained in the study by Turner et al [18] In DCIS, there are not many studies that describe the relation between p53 immunoreactivity and LR.…”
Section: Discussionsupporting
confidence: 72%
“…In addition, 5-year follow-up results concerning the impact of P53 and PS6K status on locoregional control Several studies have examined the relation between P53 overexpression and local breast tumour recurrence. A case -control study of 66 women with local breast tumour relapse following lumpectomy and radiation therapy showed that p53 overexpression was an independent predictive factor for ipsilateral breast tumour recurrence (IBTR) (Noguchi et al, 1997). Recent studies conducted by Turner et al (2000) and Zellars et al (2000) demonstrated predictive significance of P53 overexpression for locoregional recurrence in patients who underwent breast-conserving therapy, as well as in patients who underwent mastectomy.…”
Section: Discussionmentioning
confidence: 99%
“…They found that bcl-2 negativity carried a 17 times higher risk of local recurrence in patients >50 yr (10). Noguchi et al (9) and Turner et al (15) conducted similar case-control studies and noted the association between local recurrence and p53 positivity. However, a case-control approach has the limitation of inevitable biases in selecting control cases although the process is random.…”
Section: Discussionmentioning
confidence: 81%
“…Aforementioned case-control studies noted a higher risk of distant metastases in patients with p53 expression (9,15). Again, however, consecutive populationbased studies failed to verify the relationship, despite the larger number of patients and events (11,17).…”
Section: Probability (%)mentioning
confidence: 99%
See 1 more Smart Citation